VELOCITY MEDIA STORAGE TECHNOLOGY UNIVERSAL SERIAL BUS (USB) FLASH DRIVE - Deni Wijaya Indra; Fivtatianti H, SKom, MM Fivtatianti H, SKom, MM (Jurnal Sistem Komputer, 2007)
USB flash drives are NAND-type flash memory types combined with a USB 1.1 or2.0 and used as data storage devices smaller and lighter. Because of the sophisticationthat has made USB flash drives becoming popular as an alternative replacement morefloppy that has been used for data storage.Today the size of the smaller USB flash drives with between 4-7cm long and has athickness of only 0.5-1 cm. In hand of user can put pants or shirt. No surprise that thisis now a USB flash drive is not only popular among the IT course, this one device hasbeen very, very popular until the elementary school level was already familiar withthe USB Flash Drive as a storage medium.